Ballroom, Boogie, Shimmy Sham, Shake : A Social and Popular Dance Reader - Malnig, Julie (Book collections on Project MUSE., 2009)
"This dynamic collection documents the rich and varied history of social dance and the multiple styles it has generated, while drawing on some of the most current forms of critical and theoretical inquiry. The essays cover different historical periods and styles; encompass regional influences from North and South America, Britain, Europe, and Africa; and emphasize a variety of methodological approaches, including ethnography, anthropology, gender studies, and critical race theory."--Back cover.